APPLICATION OF RADIO-WAVES COAGULATION TECHNIQUE FOR THE TREATMENT OF HEMANGIOMAS OF THE MAXILLOFACIAL AREA - O.V. Gurzhiy; I.M. Tkachenko; S.V. Kolomiiets (Український стоматологічний альманах)
Statistics of the last years indicates the significant incidence of vascular neoplasms, the most of which are located at the maxillofacial area – 68–80 %, multi sites simultaneously – 20%. According to histological signs the capillary tumors are 51%, cavernous – 42%, combined – 4%, mixed – 3% of cases.